2010
DOI: 10.1088/0004-637x/721/2/1627
|View full text |Cite
|
Sign up to set email alerts
|

NEAR-ULTRAVIOLET PROPERTIES OF A LARGE SAMPLE OF TYPE Ia SUPERNOVAE AS OBSERVED WITH THESwiftUVOT

Abstract: We present ultraviolet (UV) and optical photometry of 26 Type Ia supernovae (SNe Ia) observed from 2005 March to 2008 March with the NASA Swift Ultraviolet and Optical Telescope (UVOT). The dataset consists of 2133 individual observations, making it by far the most complete study of the UV emission from SNe Ia to date. Grouping the SNe into three subclasses as derived from optical observations, we investigate the evolution of the colors of these SNe, finding a high degree of homogeneity within the normal subcl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
70
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 69 publications
(82 citation statements)
references
References 93 publications
12
70
0
Order By: Relevance
“…In the process of computing definitive photometry, science images of SN 2011iv were used for host-galaxy subtraction of SN 2007on's science images, while science images of SN 2007on were used for host-galaxy subtraction of SN 2011iv's science images. photometry is provided in Table 1; we note that the photometry of SN 2007on presented here supersedes the photometry published by Milne et al (2010).…”
Section: Observationssupporting
confidence: 63%
“…In the process of computing definitive photometry, science images of SN 2011iv were used for host-galaxy subtraction of SN 2007on's science images, while science images of SN 2007on were used for host-galaxy subtraction of SN 2011iv's science images. photometry is provided in Table 1; we note that the photometry of SN 2007on presented here supersedes the photometry published by Milne et al (2010).…”
Section: Observationssupporting
confidence: 63%
“…A comparison with observed UV light curves of SNe Ia Milne et al 2010) shows that the SN component of the model peaks brighter than most observed SNe, which show great diversity. This discrepancy is likely due to incomplete line lists for the iron-peak elements whose absorption blanket the UV (D. Kasen 2011, private communication).…”
Section: Theoretical Predictions For the Brightness Of The Shockmentioning
confidence: 86%
“…This discrepancy is likely due to incomplete line lists for the iron-peak elements whose absorption blanket the UV (D. Kasen 2011, private communication). A detailed comparison between theoretical models and the growing sample of UV photometry and spectroscopy Milne et al 2010;Bufano et al 2009;Foley et al 2012) is beyond the scope of this paper.…”
Section: Theoretical Predictions For the Brightness Of The Shockmentioning
confidence: 99%
“…Compared to SN 2009dc, SN 2005cf and other normal SN Ia are typically redder at NUV wavelengths prior to maximum light (Brown et al 2009;Milne et al 2010;Brown et al 2010Brown et al , 2012, with some fraction of "carbon-positive" events being relatively bluer at NUV wavelengths (Thomas et al 2011a;Milne et al 2013). Brown et al (2014) report the early UV colors of SN 2012dn-like events are bluer than normal as well.…”
Section: Colorsmentioning
confidence: 99%